The comparison of methylene blue and vitamin E in prevention of abdominal postoperative adhesion formation in rat uterine horn models. Biochemical and histopathologic evaluation - Yildiz, Hamit; Durmus, Ali Said; Simsek, Halil; Yaman, Ihsan (Acta Cirurgica Brasileira, 2011)
Purpose: To compare the effects of vitamin E and 1% methylen blue solutions on prevention of experimentally induced adhesions in rats. Methods: Thirty seven female Spraque Dawley rats were randomized into four groups. First group was kept as sham operated group. An adhesion model was constituted on the left uterine horn of the other groups. The lesion areas of rats from the second, the third and the fourth groups were coated with 2 ml 0.9% saline solution (C group), 10 mg vitamin E (VE group) and 1% methylen blue solutions (MB group), respectively. Results: Histopathologically, adhesion scores, mononuclear cell infiltration, oedema and fibrosis were more prominent in the MB group compared with C and VE groups. There were no significant differences between the groups in tissue glutathione peroxidase (GPx), catalase (CAT) activities and glutation (GSH) level, these parameters were slightly increased in group with VE supplementation though. The administration of VE and MB significantly decreased NO (P<0.01) levels when compared to the C group. The level of malondialdehyde (MDA) in the VE group was significantly lower (P<0.05) than those of the Sh and C groups. Conclusion: Intraperitoneal methylen blue solutions treatments were more effective according to vitamin E in preventing the formation of intra-abdominal adhesion in a rat uterine horn model.
Keywords: Vitamin E; Methylene Blue; Tissue Adhesions; Uterus; Rats